PENGARUH KUALITAS PELAYANAN DAN LOKASI TERMINAL TERHADAP KEPUASAN PENGGUNA DI TERMINAL TIPE A MANGKANG KOTA SEMARANG - Vegananda Restu Barunawati; Maesaroh Maesaroh (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2026)
Mangkang Type A Terminal is one of the land transportation hubs in Semarang City that plays an important role in supporting public mobility. However, various user reviews indicate that there is still dissatisfaction with the service and condition of the terminal location. Therefore, this study aims to analyze the influence of service quality and location on user satisfaction of Mangkang Type A Terminal in Semarang City. This study uses a quantitative approach with parametric statistical methods. Data were collected by distributing questionnaires to 100 terminal user respondents using a purposive sampling technique. Data analysis was carried out through validity and reliability tests, descriptive analysis, classical assumption tests, and multiple linear regression analysis including t-test (partial), F test (simultaneous), and coefficient of determination. The results showed that service quality (X₁) has a positive and significant effect on user satisfaction (Y) with a regression coefficient of 0.570, a calculated t value of 10.957 > t-table 1.984, and a significance of 0.000 < 0.05. Location (X₂) also has a positive and significant effect with a regression coefficient of 0.248, a calculated t value of 5.502 > t table 1.984, and a significance of 0.000 < 0.05. Simultaneously, service quality and location have a significant effect on user satisfaction with a calculated F value of 137.036 > F table 3.09 and a significance of 0.000 < 0.05. The coefficient of determination (R²) value of 0.739 indicates that 73.9% of the variation in user satisfaction can be explained by these two variables. In addition, service quality is the most dominant variable in influencing user satisfaction. Based on these findings, terminal managers are advised to improve service quality, especially in the aspects of security and comfort, as well as improve accessibility and traffic management in the terminal area to increase user satisfaction.